Motivasi Guru Honorer Dalam Mendidik Siswa Berkebutuhan Khusus - Putri, Raden Ajeng Garnes Windroyo, Aad Satria Permadi, S.Psi, MA (2016)
Education is rights and obligations for each individual. The right means anyone have a right to receive education, even children with specifically need (disabilities). Obligation means individual in general has an obligation to monitor the implementation of education. Teachers, students, facilities and infrastructure, and educational environment is a factor that influences sustainability the implementation of education. Teachers have an important role as spearheads education. Judging from the stature, not all teachers are civil servants, including non permanent teachers do not have the standart of the salary. To improve the quality of educational students with specifically need (disabilities) for motivation of teachers, including honorary teacher. Imdividuals can have different motivation as a proper of his life. The purpose of this research to konows all factor that influences motivation of teachers paid by honorarium in educate students with specifically needs. The research was done with the methods interview. Informants research as many as 6 (six) a honorary teacher who works educate students with specifically needs at remarkable school, selescted purposively of sampling consisting of 3 for female teachers who han been married, and 3 for female teachers who has not been married. The research result show virtues and social support a factor that affects motivation of honorary teacher in educating students with specifically needs. Keywords: motivation, virtues, social support, children with specifically needs